Rancang Bangun Prototipe Pengaman Kendaraan Berbasis GPS Komunikasi Pesan Telegram dan Thingspeak - Fatoni, Mukhammad; Adiananda (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2021)
Vehicle theft cases occur due to various factors, namely: minimal vehicle security system, lack of supervision and the location is easy to commit theft. In motor vehicle theft, it is often the case that the vehicle owner has difficulty tracking the vehicle carried by the thief. The creation of a vehicle safety system aims to safeguard vehicles when parking and monitor vehicle coordinates in real time integrated with the Thingspeak Web server and Telegram messages as system control. The design of the tool begins with looking for references to literature reviews, designing the system, which includes hardware design and software design, then the system will be tested. Testing and analysis includes Testing Tool Responses to Telegram Messages, GPS Signal Lock Testing, GPS Data Reading Accuracy Testing, SW-420 Vibration Sensor Testing on the System and Overall System Testing. Results of Testing Tool Responses to Telegram Messages with an average time of 19.8 seconds. Test Results of the GPS Signal Lock with an average time of 266.67 seconds. GPS Data Readout Accuracy Testing Results with an average difference of 19.99 meters. Test Results of the SW-420 Vibration Sensor in the System, if the sensor condition detects a vibration, the sensor output is High so that the buzzer is active and the Telegram message notification enters the user's Telegram account. Overall System Testing includes Testing System Control Mode and System Information Mode Testing.